2014
DOI: 10.1186/1472-6882-14-291
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophytum borivilianum (Safed Musli) root extract prevents impairment in characteristics and elevation of oxidative stress in sperm of streptozotocin-induced adult male diabetic Wistar rats

Abstract: BackgroundWe hypothesized that C. borivilianum root, known to improve male reproductive performance, prevents impairment in characteristics, morphology and elevation of oxidative stress in sperm of diabetics. We therefore investigated the effect of aqueous root extract of C. borivilianum on these parameters in diabetic rat model.MethodsC. borivilianum root aqueous extract (250 and 500 mg/kg/day) or glibenclamide (600 μg/kg/day) were administered to streptozotocin (STZ)-induced diabetic male rats for 28 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 52 publications
4
33
0
Order By: Relevance
“…Mallick et al (2007) and Singh et al (2013) also achieved good results and Giribabu et al (2014) and Shah and Khan (2014) observed that dose increase caused better recovery. Hamden et al (2008) reported that preventive treatment before the onset of diabetes was more efficient for controlling lipid peroxidation levels than the treatment with diabetic animals.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Mallick et al (2007) and Singh et al (2013) also achieved good results and Giribabu et al (2014) and Shah and Khan (2014) observed that dose increase caused better recovery. Hamden et al (2008) reported that preventive treatment before the onset of diabetes was more efficient for controlling lipid peroxidation levels than the treatment with diabetic animals.…”
Section: Resultsmentioning
confidence: 84%
“…However, only 10.4% of the studies measured oxidant levels, such as nitric oxide, nitrite/nitrate and hydrogen peroxide. Giribabu et al (2014) and Shah and Khan (2014) observed increased levels of these oxidants respectively in sperm and testicular evaluation of untreated diabetic animals. This occurs due to auto-oxidation of glucose and non-enzymatic glycation during hyperglycemia, with the subsequent increase in the production of hydrogen peroxide and superoxide radical (Chatterjee et al, 2013).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations